PENGARUH EDUKASI SUPORTIF TERHADAP TINGKAT PENGETAHUAN PASIEN HIPERTENSI LITERATUR REVIEW - ABDUL QODIR (LPPMK STIKES Widyagama Husada, 2022)
Hypertension or better known as high blood pressure is a condition where there is an increase in blood pressure above the normal threshold of 120/80 mmHg. It is one of the diseases with a high prevalence. One of the problems that are often encountered in the treatment of hypertension. If not treated properly, long-term hypertension can be at risk of causing complications and death. The purpose of this study was to determine the effect of supportive education on the level of knowledge of hypertensive patients based on empirical studies in the last 5 years. Methods This research uses the PICOS framework method, searching articles using Google Scholer and Science Direct. In the last 5 years, 10 Indonesian and English-language journals have been found with keywords in the search that match the inclusion and exclusion criteria. The results of this study. Based on 9 search journals, the results showed that the effect of supportive education on the knowledge level of hypertensive patients was obtained as a result of the significance value of knowledge in the intervention group of (p-value = 0.000), which means that there is a difference in the average knowledge in the group. intervention between before intervention and after intervention. While the significance value of knowledge in the control group is equal to (p-value = 0.209) which means that there is no difference in the average knowledge in the control group between before and after the intervention. The conclusion is that there is a difference in the effect of supportive education intervention between pretest and posttest on the variable level of knowledge that supportive education has a positive effect on the level of knowledge in controlling hypertension. Keywords: Supportive education, level of knowledge and hypertension.